Collaborative Learning in Web 2.0: The educational challenge in high school - D. Rodrigo-Cano; I. Aguaded Gómez; F.J. García Moro (Red U, 2019)
The change in higher education caused of ICT have a clear reflection on the methodologies in the university classroom. The technological opportunities and of the easy access to the Internet and information allows both teachers and students to share spaces of the university as ubiquitous environments, facilitating e-learning and blended learning. Social networks such as Facebook, Youtube and other social networks have arrival to the university classroom, both individually and in groups. We present in this paper the results of study whose aim has sought to identify collaborative methodologies in Web 2.0 from the universities of Cadiz, Huelva and Seville. We use a quantitative and qualitative mixed method based on a survey which was responded by 537 students from universities under study. Moreover, it was developed a Focus Group at each university under study, which involved 20 teachers. The results show that collaborative methodologies in university are highly regarded among team members and between them and teachers. However, these collaborative methodologies in Web 2.0 are not used and are hardly used through Web 2.0 tools. In the same direction it is shown that both teachers and university students consider social networks as excellent for collaboration  among students and between students and teachers themselves.